The performance use waste glass in concrete tile - Noriha, Abdullah (2013)
Most of glass bottles are not recycled and it's have dumped at landfill. This can cause problem to the environment. The recycling of waste glass as a source of aggregate for the production of concrete product such a tile has attracted the construction industry due its mechanical characteristics and interesting colour. From this consideration, concrete tiles with recycled glass are produced and evaluated through compressive strength and water absorption test. In this study, crushed glass has been mixed with non-resin mineral namely silica sand and white cement by replaced it with sand by 65%, 70% and 85% of glass waste. Mortar cubes with dimension 50 mm x 50 mm x 50 mm were prepared in laboratory in order to evaluate the properties of hardened concrete at difference ages which has been specific at 7, 28, and 90 days age of curing. All the cement mortar mixtures were used water - cement ratio of 0.50. The test results have shown gradual reduction in compressive strength when the content of waste glass is increased. Concrete tile made with 65% aggregate replacement with fine waste glass has better strength and lower water absorption compare other mixes. The study indicates concrete tile containing waste glass can be developed and it has fuilfill the minimum requirement of construction material. As conclusion, glass bottles waste can be used as a new raw material in high concrete tiles grade and it can reduce the consumption of landfill cost which is good the environment.